Aetiology, risk factors and immediate outcome of bacteriologically confirmed neonatal septicaemia in Mulago hospital, Uganda - Mugalu, J.; Nakakeeto, M.K.; Kiguli, S.; Mulindwa, Deo H. Kaddu (African health sciences,, 2006)
Neonatal septicaemia remains a major cause of morbidity and mortality. The aetiology, risk factors and outcome of this problem need to understood.To determine the aetiology, risk factors and immediate outcome of bacteriologically confirmed septicaemia in Mulago hospital.Blood cultures were aseptically obtained from neonates presenting with clinical sepsis by WHO criteria to Mulago during a five month period between July and November 2002. Blood was placed in Brain Heart Infusion media and incubated within 30 minutes. Subcultures were plated daily up to 7 days on blood, chocolate and MacConkey agar and incubated in aerobic and 5% carbon dioxide conditions. Pure colonies were identified by Gram stain and biochemical tests and antibiotic sensitivities were obtained.Gram positive organisms were predominant (69.2%) followed by E. coli (17%) and Group B Streptococci (GBS) (7%).Staphylococcus aureus and E. coli dominated isolates in early and late onset sepsis. S. aureus was more sensitive to gentamicin than to cloxacillin. The sensitivity of E. coli to ceftriaxone was 94.1%.Factors significantly associated with neonatal septicaemia were male sex, history of convulsions, hypoglycaemia, lack of antenatal care, late onset sepsis and umbilical pus discharge. Mortality in sepsis cases was 18.1%, and 84% of deaths occurred in the first 2 days of admission. Hypoglycaemia was significantly associated with death (p < 0.01).S. aureus predominates the aetiology of neonatal septicaemia followed by E.coli. Most deaths occur in the first 48 hours of admission and hypoglycaemia is significantly associated with death.